Morning Glory Anomaly: A Rare Case - A. Balraj; Saloni Mahesh Joshi (Delhi Journal of Ophthalmology)
Morning glory anomaly is a rare malformation of the optic nerve, presenting with or without systemic associations. The low prevalence of this entity makes it tricky to diagnose. Proper counseling regarding the prognosis and treatment is needed for these patients along with screening of family members. Efforts for a holistic approach toward diagnosis and treatment would deliver better care toward patient.